Análise dos parâmetros para a tomada de decisão na mobilidade urbana segundo o problema custo – conforto – conveniência - Lobato, Beatriz Cardoso (2020)
This work aims to analyze how individuals make the decision on urban mobility taking into account cost, comfort and convenience. The systematic literature review (SLR) methodology was applied, in which 113 articles were selected that had adherence to urban mobility and costs. Subsequently, the main authors were defined, in which the study by the author Fishman, 2017, stood out. In the authors with greater connection, with several studies, the author Cattaneo stood out, the SLR also showed that the theme addressed is relatively new, with 77% of these studies are concentrated between the years 2015 to 2019. The publications are distributed all over the world, highlighting the European continent which concentrates 44.44% of the studies on mobility, after systematization, the most used methodologies by the researchers were identified, which were, mostly, statistical analysis methods and critical literature review. From these definitions, it was identified the need to apply a tool that could give choice’s parameters for the users of transport modals to be able to compare in a quantitative way and choose which type of transport is more viable according to their needs. In this context, the AHP method (Analytic Hierarchy Process) was selected, as it provides the comparison of criteria and sub-criteria for decision making. After the definition of an acceptable sample, the method was applied and the answers analyzed individually and the definition of which transport modal would be most recommended to each person, according assigned amount, taking in consideration cost, comfort and convenience was found as result. The users between 18 and 50 years old preferred the criteria cost, but whem they evaluate the subcriterias the modal own vehicle was suggested as result. In the other hand, the users between 61 and 70 years old it was suggested the modal app service and the preferred criteria was the comfort, showing the method effectiveness to theme adressed.